การปรับเปลี่ยนมุมมองของอินเดียต่อโครงการขุดคลองไทย - เนตรทราย อ่วมงามอาจ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This thesis aims to study the India’s changing perspective towards Thai Canal project by analyzing India’s perspective change, the history of the conflict between China and India affecting the National security including the National interest of India through the Thai Canal project dimension. For the main factor is the new context in which China has influenced on the neighboring countries of India that are the important strategic areas of India that are the Indian Ocean region through the 21st Century Silk Road Strategy. Thai Canal project is the one of China’s expectation as China has been trying to precipitate it into the economic corridors on the seabed. China s proactive action together with the ambiguous attitude of Thailand and China for the implementation of this project including the committed loaning or funding for this infrastructure project in case the agreement is not met or dealt make China will negotiate and control this project by themselves. As this result, India is currently worrying and changing their perspective on the Thai Canal project that may affect the stability of the region, National security and Interest of India.